2015
DOI: 10.1093/tropej/fmv037
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Experiences of Physical, Emotional and Sexual Abuse among College Students in South India

Abstract: Emotional, physical and sexual abuse is common in childhood and demands prompt interventions at the familial, community and political levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 13 publications
1
10
0
2
Order By: Relevance
“…Previous studies examining CSA among college students in India have reported rates ranging from 4% to 55%. [ 1 4 13 14 ] Our prevalence rates are comparable to the meta-analysis that reported the prevalence of CSA, across the world, to be 12.7%, when only self-report studies were examined. [ 15 ] In our study, sexual abuse was significantly higher among the male students compared to females whereas the studies from western countries have consistently reported higher rates among females.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies examining CSA among college students in India have reported rates ranging from 4% to 55%. [ 1 4 13 14 ] Our prevalence rates are comparable to the meta-analysis that reported the prevalence of CSA, across the world, to be 12.7%, when only self-report studies were examined. [ 15 ] In our study, sexual abuse was significantly higher among the male students compared to females whereas the studies from western countries have consistently reported higher rates among females.…”
Section: Discussionsupporting
confidence: 73%
“…This number matches with that of a study from South India done among college students (10%). 20 A large-scale study conducted in Sweden revealed that the disclosure rate among sexually abused girls was 81% and boys was 69% among high school seniors. They most often disclosed with friends of the same age and few with professionals and authorities.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Similarly, in a survey done in college students of Pondicherry, there were significant statistical differences in the proportions of emotional abuse, based on gender (females were name-called and neglected twice as much as males). [ 12 ] Several studies have described the association of EDs with a history of childhood abuse in a significant number of individuals. One study reported that up to half of the patients with EDs had a history of childhood abuse or trauma,[ 13 ] while another study found that 48% of the patients admitted for anorexia nervosa reported a history of sexual abuse during their childhood.…”
Section: Discussionmentioning
confidence: 99%